The Ideological Implication of Objectives Formulated within the Area of Education - Teresa Hejnicka-Bezwińska (Nicolaus Copernicus University in Toruń, 2012)
The politicization of the process of introducing pedagogics as a scientific discipline into university structures at the turn of the 18th and 19th centuries, made it particularly prone to being exploited. The current cultural changes, including the changes taking place in science and social educational practices, enable overcoming this disadvantageous implication. The model of relationship between various types of knowledge about education and social educational practices which is presented in this article, demonstrates that there is no direct relationship between scientific knowledge about education and social educational practices. One can say that contemporary pedagogics does not form educational practices, but researches it and reveals through the research process the ideological implications of objectives formulated and achieved within the area of education. Hence, it provides the subjects of social discourse about education with well verified premises.